Traumatismos na dentição decídua: prevalência, fatores predisponentes e repercussão sobre a qualidade de vida - Flavia de Carvalho Oliveira Robson (2004)
A greater understanding of the prevalence of trauma in the deciduous dentition is important for the development of measures with the objective of reducing their occurrence and also treating them with the necessary care. Thus the objective of this study was to evaluate the epidemiological profile of deciduous dental trauma in the pre-school population of Belo Horizonte Minas Gerais, Brazil, investigating the influence of a number of biological variables as predisposing factors of dental trauma and in addition its repercussions on the quality of life of these children. 419 boys and girls participated in the study who were enrolled in state and private schools as well as nurseries, in an age group up to five years of age. The sample was divided proportionally between regions and types of school. The eighteen institutions visited were chosen by random selection. The data collection consisted of the application of a questionnaire to all parents concerning any history of dental trauma and the Oral Health Impact Profile 14 (OHIP-14) was applied to the parents/guardians of children who reported dental trauma, as well as the clinical examination of the children. Two pilot studies were used to test the study design. The research had ethical approval from the Comitê de Ética em Pesquisa da UFMG and the parents/guardians signed a free and informed consent. The rate of return was 80.6%. The data were processed using the SPSS 8.0 package and Statxact 3.0. Chi-squared, Fisher exact test and Fisher-Freeman-Halton test were carried out for univariate analysis and the model of logistical regression for multivariate analysis were applied at the 5.0% level of significance. The results revealed that: trauma of the deciduous dentition affected 39.1% of the study population, and the enamel fracture was the most common lesion (49.7%); boys were 1.43 times more likely to present with trauma of deciduous teeth when compared to girls; children with an overjet greater than three mm have three times more chance of trauma to teeth than children whose overjet is less or equal to three mm; the chance of a child with incompetent lips suffering trauma is twice as great as the chance of a child with competent lips having the problem; the repercussions of trauma to the deciduous dentition on quality of life for children was low and was not associated with the severity of the trauma; children of a less favoured socio-economic group suffered greater repercussions as a result of dental trauma on the quality of their lives; boys with an overjet greater than three mm and incompetent lips had a 74.65% chance of suffering trauma to their deciduous dentition. Further studies should be developed with an emphasis on the repercussions of trauma to the deciduous dentition on the quality of life for children.